Retroperitoneal germ cell tumor mimicking neoplasm of ampulla of Vater - Vega, Rodrigo Velázquez-de la; Díaz-Flores, Aarón; Trejo-Ávila, Mario E.; Bada-Yllán, Orlando; Delano-Alonso, Roberto; Valenzuela-Salazar, Carlos (International Surgery Journal, 2018)
A 20-year-old man previously healthy, presented to the emergency department for evaluation of obstructive jaundice, backache and weight loss. Abdominal ultrasonography demonstrated a dilated common bile duct (up to 2 cm), increased gallbladder dimensions (10.3 x 4.9 cm) with biliary sludge. Computed tomography of the abdomen showed a retroperitoneal tumor with 18 x 14 cm dimensions, and numerous large retroperitoneal lymph nodes. The liver demonstrated a bilateral intrahepatic bile duct dilatation. An endoscopic retrograde cholangiography was performed. The study revealed an ulcerative neoplasm of ampulla of Vater, and the cholangiogram obtained images of dilated extra-hepatic and intra-hepatic bile ducts with a large stenosis in the distal third of the common bile duct. After biopsies were analyzed, the definite diagnosis was a retroperitoneal extragonadal germ cell tumor (subtype: embryonal carcinoma) with infiltrative invasion to duodenal wall. A testicular ultrasonography ruled out a testicular tumor. Endoscopic stenting was necessary for decompress the unresectable malignant bile duct obstruction. Patient was referred for cisplatinum based chemotherapy.